The Role of Success Factors for Using Information Systems in Achieving Organizational Excellence in the Greater Amman Municipality - Al-Hyasat, Hasan Khaled Abed (Jordan Journal of Business Administration, 2022)
The purpose of this study is to identify the role of information systems using success factors with their dimensions (system quality, information quality, service quality, top management support and user efficiency) in achieving organizational excellence in Greater Amman Municipality (GAM). This study tries to provide recommendations that contribute to progress in organizational excellence levels. The study adopted a simple random sample from the study population of (323) information system users in (GAM). Descriptive analytic methods were used to describe sample responses and collect data. The study revealed the existence of a statistical significant effect at a significance level of (α≤0.05) of the information system using success factors on achieving organizational excellence. The study recommended the need for GAM to maintain continuous interest in successful use of information systems, considering these systems as a strategic resource that enables to achieve progress in levels of organizational excellence. He also recommended that senior management adopts effective policies for change and development in organizational tasks and turns them into action procedures to raise performance values through making the best use of technical resources.